Development of chitosan based microencapsulated spray dried powder of tuna fish oil: oil load impact and oxidative stability - S. Kanwal; M. Hafeez-ur Rehman; A. Hussain; M. Nadeem; F. Abbas; M. Akram; M. Inayat; F. Sughra; K. Ali (Brazilian Journal of Biology, 2021)
Abstract The impact of fish oil concentration on the oxidative stability of microcapsules through the spray drying process using chitosan and maltodextrin as wall material was studied. Emulsions were prepared with different Tuna fish oil (TFO) content (TFO-10%, TFO20%, TF030% TF0-40%) while wall material concentration was kept constant. Microencapsulated powder resulting from emulsion prepared with high fish oil load have high moisture content, wettability, total oil and low encapsulation efficiency, hygroscopicity and bulk tapped density. Oxidative stability was evaluated periodically by placing microcapsules at room temperature. Microcapsules prepared with TFO-10% presented high oxidative stability in terms of peroxide value (2.94±0.04) and anisidine value (1.54±0.02) after 30 days of storage. It was concluded that optimal amounts of fish oil for microencapsulation are 10% and 20% using chitosan and maltodextrin that extended its shelf life during study period.